O idoso e as políticas sociais estudadas no contexto asilar em Porto Velho - Silva, Arthelúcia Maria Amaral da (2005)
He present study it had the objective to investigate the perception of the aged people living in institution to put in a home on the reach of the assistenciais politics the one that has right. One is about an empirical study, involving the application of the fenomenológico method through which one searched to catch the perception of 30 citizens investigated on aged and the social politics studied in the context to put in a home in Porto Velho-RO The used theoretical clipping involved a boarding on the phenomenon of the aging in the world, Brazil and the state of Rondônia, as well as an analysis of the public politics that attend the aged ones, treating since the first initiative in 1974, through would carry n.º 82/74 of the Ministry of the Providence and Assistance Social (MPAS), standing out the Constitution of 1988 as more important landmark in the delineation of these politics that had culminated with the approval of the national politics and with the Statute of the Aged one. The analyzed data had shown that the aged ones had considered the institution to put in a home investigated as being good and the given assistance as being adjusted às its necessities, even so believe that the aged situation do no Brazil is bad, therefore the family are not fulfilling its paper and that they are unaware of the public politics that guarantee its rights. The study it concludes that the state of Rondônia, through the FASER, is creating mechanisms that they aim at to guarantee the social rights of the aged population that shelters.